Optimal entry to an irreversible investment plan with non convex costs - Tiziano De Angelis; Giorgio Ferrari; Randall Martyr; John Moriarty (Bielefeld University, Center for Mathematical Economics (IMW), 2016)
A problem of optimally purchasing electricity at a real-valued spot price (that is, with potentially negative cost) has been recently addressed in De Angelis, Ferrari and Moriarty (2015) [SIAM J. Control Optim. 53(3)]. This problem can be considered one of irreversible investment with a cost functional which is non convex with respect to the control variable. In this paper we study the optimal entry into this investment plan. The optimal entry policy can have an irregular boundary arising from this non convexity, with a kinked shape.
urn:nbn:de:0070-pub-29047569
Keywords: C61; D92; E22; Q41; 330; continuous-time inventory; optimal stopping; singular stochastic control; irreversible investment; Ornstein-Uhlenbeck price process